Development of lectin gene-based SNAP and ARMS markers as anticancer biomarkers in mutant rodent tuber (Typhonium flagelliforme) of Pekalongan accession, Indonesia - ZIDNI MUFLIKHATI; Nesti F. Sianipar; Reflinur Reflinur; Anas Anas (Society for Indonesian Biodiversity, 2025)
Abstract. Muflikhati Z, Sianipar NF, Reflinur, Anas. 2025. Development of lectin gene-based SNAP and ARMS markers as anticancer biomarkers in mutant rodent tuber (Typhonium flagelliforme) of Pekalongan accession, Indonesia. Biodiversitas 26: 424-433. Typhonium flagelliforme is a medicinal plant with potential anticancer properties. This study aimed to develop Single Nucleotide Amplified Polymorphism (SNAP) and Amplification Refractory Mutation System (ARMS) markers from the lectin gene that contributed to anticancer activity found in gamma-irradiated mutant rodent tuber plants of the Pekalongan accession. The two markers were designed for the site of Single Nucleotide Polymorphisms (SNPs), which were identified at approximately 500 bp in the length of the lectin gene sequence. The SNAP Lec113 primer designed from a 113 bp silent mutation in the respective gene has successfully differentiated rodent tuber mutant lines across the wild-type, determined by the specific T allele at 351 bp. Meanwhile, the ARMS Lec241 primer, designed from a 241 bp missense mutation (arginine to threonine), distinguished mutants from their wild-type by the specific G allele at 193 bp. The two developed markers demonstrated their high specificity and sensitivity in detecting genetic variations spanning lectin gene involved in anticancer biosynthesis. The SNAP marker effectively distinguished among seven mutant samples, while the ARMS marker provided consistent results across experiments. These molecular markers offer a rapid and accurate method for identifying genetic variations in rodent tuber plants, providing a significant practical benefit for the field of genetic screening and mutation impact studies. The three-primer SNAP system presents a more cost-effective option for large-scale screening compared to the four-primer ARMS system. This study provides a foundation for targeted breeding programs and genetic studies in rodent tuber, potentially accelerating the development of varieties with enhanced medicinal properties. The markers enhance genetic screening efficiency and understanding of medicinal properties in rodent tuber, significantly advancing the field of natural product therapeutics and mutation impact studies.